1996
DOI: 10.1149/1.1836639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an External Electric Field from a Substrate on Conductance of SnO2 Thin Films

Abstract: Thin Sn02 films of about 10 nm thickness were prepared by sputtering on Si02/Si substrates, and the effects of an external electric field from the substrate on the conductance of the SnO., film were investigated at 26°C and up to 300°C. The apparent conductance of the Sn02 film increased with a positive substrate bias and decreased with a negative substrate bias. These field effects became more evident with larger bias and in 5n02 films with a lower carrier concentration. By using metal oxide semiconductor the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[15][16][17][18][19] This subject was revisited in connection with the development of FET-based gas sensors. [20][21][22][23] The latter property was inferred from the field dependence of the work function…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] This subject was revisited in connection with the development of FET-based gas sensors. [20][21][22][23] The latter property was inferred from the field dependence of the work function…”
mentioning
confidence: 99%
“…Experimental observations, supported by calculations, suggest that the availability of electrons at the vacancy site affects the chemical activity of the oxide surface. ,, The influence of an electrostatic field (and the concomitant change in the near-surface electron density) on adsorption and catalysis occurring on macroscopic semiconductor surfaces was predicted and experimentally verified long ago. This subject was revisited in connection with the development of FET-based gas sensors. The latter property was inferred from the field dependence of the work function (or channel conductance) change upon the adsorption of a molecule to an oxide surface configured as a field-effect transistor (FET) with a chemically active gate.…”
mentioning
confidence: 99%
“…The electron mobility should, consequently, be considered. In the previous letter, 12 it was suggested that a decrease of the current under a negative substrate bias is caused by a high resistive depletion layer formed at SnO 2 /SiO 2 interface. However, it was not confirmed whether the electron mobility is kept constant or not.…”
Section: Yoshiko Niki Kunishima and Masaru Miyayamamentioning
confidence: 99%